Inventarisasi dan Identifikasi Cendawan Patogen Pada Tanaman Pisang Rutai (Musa borneensis) - Iin Arsensi; Abdul Rofik (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
One type of fruit typical of Kutai who now also started rare is Rutai bananas. Rutai Bananas that having small size is very well liked, besides the smell also taste sweet with a high vitamin content.Small fruit shape of Rutai bananas was fit to be an appetizer at the restaurant or diner. There is even a plan to make Rutai banana as an appetizer that must be in Kutai Kartanegara Regency.The purpose of this study was to determine the symptoms and signs of disease caused by specific pathogens in Rutai banana plants and fungi potentially pathogenic on it.The experiment was conducted in people's gardens banana growing areas in Muara Badak Rutai Kutai Kartanegara Regency, East Kalimantan Province, by calculating the frequency and intensity of attacks pathogens on Rutai banana plants. Identification of pathogens carried out at the Laboratory of Agriculture Faculty of Agriculture, University of Widyagama.This study is expected to be a reference to know the symptoms, signs of the disease in Rutai banana plants; Increasing community participation to preserve rare plants; Support government programs to preserve rare plants either fruit or trees. Help disseminate to public about the benefits of eating Rutai banana especially for health.